Aktualisasi Nilai Aqidah dan Etos Kerja Mahasiswa Aqidah dan Filsafat Islam dalam Kegiatan Magang di Kantor Urusan Agama (KUA) Kecamatan Medan Kota (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the actualization of Islamic creed (aqidah) values and work ethic among students of the Aqidah and Islamic Philosophy Department, Faculty of Ushuluddin and Islamic Studies, UIN Sumatera Utara Medan, during their internship program at the Office of Religious Affairs (KUA) of Medan Kota District. This research employs a qualitative descriptive approach using observation, interviews, and documentation techniques. The findings indicate that aqidah values such as honesty, trustworthiness, sincerity, and responsibility are manifested in administrative tasks, religious counseling activities, and public religious services. Furthermore, the Islamic work ethic of the students is reflected in discipline, professionalism, cooperation, and commitment to work quality. The integration of aqidah values and work ethic fosters a service-oriented and devotional work pattern, indicating that the internship program serves not only as practical learning but also as a medium for internalizing Islamic values within the context of public religious services.